Indeks Kedalaman dan Keparahan Kemiskinan di Provinsi Nusa Tenggara Barat dan Penanganannya Dalam Ekonomi Islam - Irwan, M (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
This study aims to determine: Number of Population classified as poor, Depth Index and Poverty Severity in West Nusa Tenggara Province and Handling in Islamic Economy. The research method used is descriptive method, the data used secondary data and analysis tools used is the technique of growth analysis. The results showed that the condition of poverty in West Nusa Tenggara is seen from the number of population decreased with negative growth average 3,19 percent. Percentage of population in 2016 amounted to 16.02 percent. Rural poor are 14.82 percent and 17.55 percent for urban areas by 2016. The poverty line for the urban poor is Rp 346,581 while for rural areas Rp 328,775, - by 2016. Depth Index (P1) poverty in NTB in 2016 of 2,626 indicating that the economic conditions of the poor are in an improved condition. The Poverty Severity Index (P2) in NTB in 2016 is 0.653 in 2016 which indicates the inequality of expenditure of the poor is narrowed. Poverty alleviation in Islam can be done one of them through zakat command. Baznas West Nusa Tenggara Province has been able to raise funds Zakat, Infaq and Shadaqah (ZIS) and contribute in poverty alleviation in West Nusa Tenggara. The amount of ZIS funds collected in 2016 reached Rp 8,288,499,700, - from the target of Rp 7.500.000.000, -.